The association between dietary fatty acid intake and the risk of developing preeclampsia: a matched case–control study - Shu-na Li (Nature Portfolio, 2021)
Abstract The association between dietary fat intake during pregnancy and the risk of developing preeclampsia has been examined in many epidemiological studies, but the results remain inconsistent. The aim of this study was to clarify this association in pregnant Chinese women. After conducting 1:1 matching, 440 pairs consisting of pregnant women with preeclampsia and hospital-based, healthy pregnant women matched by gestational week (± 1 week) and age (± 3 years) were recruited. A 79-item semi-quantitative food frequency questionnaire administered during face-to-face interviews was used to estimate the participants’ dietary intake of fatty acids. We found that the intakes of arachidonic acid (AA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) were inversely associated with the risk of developing preeclampsia. Compared with the lowest quartile intake, the multivariate-adjusted odds ratios (95% confidence interval) of the highest quartile intake were 0.42 (0.26–0.68, p-trend < 0.001) for EPA, 0.52 (0.3–0.83, p-trend = 0.005) for DHA, and 0.41 (0.19–0.88, p-trend = 0.007) for AA. However, we did not observe any significant associations between the intake of total fatty acids, saturated fatty acids, and mono-unsaturated fatty acids and the risk of developing preeclampsia. Our results showed that the dietary intake of long-chain polyunsaturated fatty acids (i.e., EPA, DHA, and AA) may protect pregnant Chinese women against the development of preeclampsia.